Beyond morbidity and mortality in reintroduction programmes: changing health parameters in reintroduced eastern bettongs Bettongia gaimardi. Issue 4 (28th March 2016) - Portas, Timothy J.; Cunningham, Ross B.; Spratt, David; Devlin, Joanne; Holz, Peter; Batson, William; Owens, Jane; Manning, Adrian D.
Abstract: The eastern bettong Bettongia gaimardi, a potoroid marsupial, has been extinct on the Australian mainland since the 1920s. Sixty adult bettongs were reintroduced from the island of Tasmania to two predator-free fenced reserves on mainland Australia. We examined baseline health parameters (body weight, haematology and biochemistry, parasites and infectious disease exposure) in a subset of 30 (13 male, 17 female) individuals at translocation and again at 12–24 months post-reintroduction. The mean body weight increased significantly post-reintroduction but there were no significant differences in body weight between the two reintroduction sites or between the sexes in response to reintroduction. Differences were evident in multiple haematological and biochemical variables post-reintroduction but there were few differences between the two reintroduced populations or between the sexes in response to reintroduction. Ectoparasite assemblages differed, with five of 13 species failing to persist, and an additional four species were identified post-reintroduction. None of the bettongs had detectable antibodies to the alphaherpesviruses Macropodid herpesvirus 1 and 2 post-reintroduction, including one individual that was seropositive at translocation. Similarly, the novel gammaherpesvirus potoroid herpesvirus 1 was not detected by polymerase chain reaction (PCR) in any of the bettongs post-reintroduction, including one individual that was PCR-positive at translocation. None of the bettongs had detectable antibodies to Toxoplasma gondii either at translocation or post-reintroduction. Our data demonstrate changing baseline health parameters in eastern bettongs following reintroduction to the Australian mainland are suggestive of improved health in the reintroduced populations, and provide additional metrics for assessing the response of macropodoids to reintroduction.